2022
DOI: 10.1186/s13046-022-02520-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts and osteoclasts: an important switch of tumour cell dormancy during bone metastasis

Abstract: Bone metastasis occurs when tumour cells dissociate from primary tumours, enter the circulation (circulating tumour cells, CTCs), and colonize sites in bone (disseminated tumour cells, DTCs). The bone marrow seems to be a particularly dormancy-inducing environment for DTCs, yet the mechanisms of dormancy initiation, reactivation, and interaction within the bone marrow have to be elucidated. Intriguingly, some evidence has suggested that dormancy is a reversible state that is switched ‘on’ or ‘off’ depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Despite growing knowledge that BM niche cells strongly influence tumor dormancy and activation, many of the specific interactions by which BM niche cells influence BCC function remain unclear, owing in part to in vivo microenvironment complexity (e.g., bone remodeling processes that occur with aging or injury leading to a range of dynamic cell-cell and cell-matrix interactions) ( 6 , 34 ). Reductionist model systems provide an opportunity to control aspects of this complexity and dissect interactions between niche cells and DTCs ( 18 , 19 , 38 ), with a focus to date on examining interactions between mixed populations of BCCs and niche cells in direct coculture (i.e., direct BCC–niche cell contact) ( 29 32 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite growing knowledge that BM niche cells strongly influence tumor dormancy and activation, many of the specific interactions by which BM niche cells influence BCC function remain unclear, owing in part to in vivo microenvironment complexity (e.g., bone remodeling processes that occur with aging or injury leading to a range of dynamic cell-cell and cell-matrix interactions) ( 6 , 34 ). Reductionist model systems provide an opportunity to control aspects of this complexity and dissect interactions between niche cells and DTCs ( 18 , 19 , 38 ), with a focus to date on examining interactions between mixed populations of BCCs and niche cells in direct coculture (i.e., direct BCC–niche cell contact) ( 29 32 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…BCC switching to proliferation from growth inhibition was observed in these indirect coculture exchange studies and suggested the importance of soluble secreted factors (e.g., cytokines, chemokines, and growth factors) ( 45 , 47 ) in dormancy/reactivation. In vivo, osteoblasts are known to be critical in both bone homeostasis and repair processes, while MSCs are present in the BM and recruited/expanded in bone injury and remodeling processing ( 6 , 34 , 71 ): The 3D indirect coculture model provides future opportunities for further capturing and probing these complex interactions in dormancy/reactivation (e.g., tricultures of BCCs, hFOBs, and hMSCs and triggering/examining matrix remodeling).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…XN has also been shown to regulate the levels of osteoclastic genes during RAW264.7 cell osteoclastogenesis [30]. Osteoblast-regulated bone formation induces and maintains tumor cell dormancy [31]. Therefore, it remains to be explored whether XN can also regulate osteogenesis-related processes and thus OS progression.…”
Section: Discussionmentioning
confidence: 99%